THE DEVELOPMENT OF PROBLEM-BASED PSYCHOTROPIC AND ADDICTIVE SUBSTANCE LEARNING KITS 2 1 TO IMPROVE THE STUDENTS’ METACOGNITION - Nur Hanifah (Jurnal Cakrawala Pendidikan, 2016)
Abstract: This study was aimed to develop problem-based psychotropic and addictive substance learning kits to improve the students’ metacognition and concept mastery. The kits were developed in three stages (define, design, develop). The “develop” stage used the non-equivalent control group design. The subjects were grade VIII students of SMP Nasima, Semarang. The findings of the study showed that the developed learning kits were valid in the very good category. The mastery of concepts and metacognition improved with an average percentage of N-gain for the experimental group with the high category. The result of the questionnaires on metacognition showed the N-gain percentage of the experimental group belonging to the fair category. The students’ ability to solve problems and the implementation in the small class and in the experimental group in the first and fourth meetings were in the good category. The students and teacher gave positive responses to the developed learning kits and its implementation in the class.The findings showed that the problem-based learning can be used for improving students’ metacognition. Keywords: Problem-based learning, metacognition, addictive and psychotropicsubstances PENGEMBANGAN PERANGKAT PEMBELAJARAN ZAT ADIKTIF DAN PSIKOTROPIKA BERBASIS MASALAH UNTUK MENINGKATKAN METAKOGNISI SISWA Abstrak: Tujuan penelitian ini adalah menghasilkan perangkat pembelajaran zat adiktif dan psikotropika berbasis masalah yang teruji mampu meningkatkan metakognisi dan penguasaan konsep siswa. Pengembangan perangkat pembelajaran menggunakan tiga langkah pengembangan (define, design, develop). Tahap develop menggunakan desain Non equivalent Control Group Design. Subjek penelitian adalah siswa kelas VIII SMP Nasima Semarang. Hasil penelitian menunjukkan bahwa perangkat pembelajaran yang dikembangkan valid dengan kategori sangat baik. Penguasaan konsep dan metakognisi mengalami peningkatan rata-rata persentase N-gain kelas eksperimen dengan kategori tinggi. Hasil kuesioner metakognisi menunjukkan persentase N-gain pada kelas eksperimen dengan kategori sedang. Kemampuan pemecahan masalah dan keterlaksanaan pembelajaran pada siswa kelas kecil dan kelas eksperimen pada pertemuan ke-1 sampai ke-4 dengan kategori baik. Siswa dan guru memberikan respon positif terhadap perangkat pembelajaran yang dikembangkan dan penerapannya di dalam kelas. Hasil penelitian menunjukkan bahwa pembelajaran berbasis masalah dapat digunakan untuk meningkatkan metakognisi siswa. Kata Kunci: pembelajaran berbasis masalah, metakognisi, zat adiktif dan psikotropika